Evaluation of Parameters Accelerating the Aging of PEMFCs Operating under Reformate Containing Carbon Monoxide. Issue 6 (6th April 2018) - Profatilova, Irina; Jacques, Pierre-André; Escribano, Sylvie
Abstract : Development of efficient accelerated stress test protocols for polymer electrolyte membrane fuel cells (PEMFCs) is an extremely important topic closely related to FC lifetime prediction and a decrease of the FC test costs. This work is dedicated to precise investigation of the impact of various accelerating factors on a FC performance over 1000 h scale. Five identical membrane electrode assemblies with Pt-based catalysts on the cathode and PtRu-based catalyst on the anode were studied using load cycling protocols. The impact of accelerating aging stressors and their combinations, such as carbon monoxide in fuel, frequency and amplitude of current cycling and regular electrochemical diagnostics via polarization curves and cyclic voltammograms measurements was thoroughly investigated. In addition, electrochemical cell behavior under fixed and varied fuel compositions is addressed. Total and irreversible cell performance losses are quantified for different aging tests. It is shown that the importance of aging factors can change depending on a test duration. This study combines large amount of experimental electrochemical data giving quantitative ranking for the importance of factors accelerating cell aging in operation conditions close to real ones for stationary fuel cells.